Book Review of "The Future of War" by Lawrence Freedman - Jonathan A.S. Honig (International Journal of Nuclear Security, 2019)
The Future of War, by Lawrence Freedman, is a comprehensive work on warfare, its evolution, and its predicted future course which is appropriate for experts and novices alike. Published in 2017, this book contains both historical and contemporary examples of warfare right up to such recent events as the Syrian civil war and the advent of the self-styled Islamic State group. This book is in its first edition and is an excellent marshaling of information on a varied and complex subject.